Mitochondrial Dysfunction, Macrophage, and Microglia in Brain Cancer - Lu, Rongze Olivia; Ho, Winson S. (Frontiers in Cell and Developmental Biology, 2021)
Glioblastoma (GBM) is the most common malignant brain cancer. Increasing evidence suggests that mitochondrial dysfunction plays a key role in GBM progression as mitochondria is essential in regulating cell metabolism, oxidative stress, and cell death. Meanwhile, the immune microenvironment in GBM is predominated by Tumor associated macrophages and microglia (TAM), which is a heterogenous population of myeloid cells that in general create an immunosuppressive milieu to support tumor growth. However, subsets of TAMs can be pro-inflammatory and thereby anti-tumor. Therapeutic strategies targeting TAMs are increasingly explored as novel treatment strategies for GBM. The connection between mitochondrial dysfunction and TAMs phenotype in the tumor microenvironment is unclear. This review aims to provide perspectives and discuss possible molecular mechanisms mediating the interplay between glioma mitochondrial dysfunction and TAMs phenotype in shaping tumor immune microenvironment.